Listening to Cambodian Rock Band: An Interview with Lauren Yee and Chay Yew - Galella, Donatella (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2020)
An interview with playwright Lauren Yee and director Chay Yew about Cambodian Rock Band, a memory play that uses music to call back to traumatic memories of the Khmer Rouge.